Mechanical calculation of overhead power line wires using sicad - Gai, O.; Martyniuk, O. (Energy and Automation, 2023)
The power transmission system is a key element of the electric power infrastructure, which ensures the uninterrupted supply of electricity to consumers. Given the importance of system reliability and efficiency, it is necessary to develop methods that save time and effort during design and provide optimal characteristics of wires. The developed automatic design and calculation system is based on computer models and algorithms that take into account various factors affecting the mechanical properties of wires of overhead power lines. Such factors include the maximum mechanical stress to which the wires are subjected due to wind forces, ice loads and other external influences, as well as electrical parameters such as current, voltage and energy losses. In addition, the system takes into account weather conditions, such as wind speed, temperature and air humidity, since these factors can affect the thermal resistance and performance of the wires. Using the automatic design and calculation system has numerous advantages. First, it allows you to significantly reduce the time required for project development and calculations. Instead of manually specifying parameters and performing complex calculations, engineers can use a system that automatically generates solutions. Secondly, the system ensures high accuracy of calculations, reducing the probability of errors that may occur during manual analysis. This contributes to the achievement of high reliability and efficiency of the power transmission system. As part of the scientific research, an approach was proposed, which is based on the mechanical calculation of overhead power line wires using SICAD CAD. The obtained results are presented in the framework of a joint technical meeting of leading specialists of operating enterprises and the team of the department of power supply named after V.M. Sinkova NULES of Ukraine.Key words: mechanical calculation of wires, design of overhead lines, automatic calculation systems